Preliminary study of the Thai-version of the Scale for the Assessment of Positive Symptoms (SAPS-Thai): content validity, known-group validity, and internal consistency reliability (Archives of Clinical Psychiatry, 2019)
Objective: To assess the psychometric properties of the Thai version of the Scale for the Assessment of Positive Symptoms (SAPS-Thai). Methods: Content validity was evaluated by four psychiatrists who rated the SAPS-Thai, and the content validity indexes (CVI) were also analyzed. Known-group validity was assessed by comparing the SAPS-Thai score among thirty outpatients and ten inpatients with schizophrenia. Internal consistency was calculated using the Cronbach’s coefficient alpha. Results: SAPS-Thai has excellent content validity, with an average-CVI of 0.92. The inpatient group had a significant higher score for both the global SAPS-Thai scores [7.4 (1.95) vs. 1.93 (1.59), p < 0.001] and total SAPS-Thai scores [21.2 (11.8) vs. 3.67 (2.87), p < 0.001] indicating good known-group validity. SAPS-Thai had a good internal consistency with a Cronbach’s alpha of 0.87. Discussion: SAPS-Thai provides a comprehensive measurement of positive symptoms and indicated content and known-group validity and a satisfactory level of internal consistency reliability.